Perspectives on the Use of New Information and Communication Technology (ICT) in the Modern Economy - Popkova, Elena G.; Ostrovskaya, Victoria N. (Advances in Intelligent Systems and Computing, 2019)
This book includes the best works presented at the scientific and practical conference that took place on February 1, 2018 in Pyatigorsk, Russia on the topic "Perspectives on the use of New Information and Communication Technology (ICT) in the Modern Economy". The conference was organized by the Institute of Scientific Communications (Volgograd, Russia), the Center for Marketing Initiatives (Stavropol, Russia), and Pyatigorsk State University (Pyatigorsk, Russia). The book present the results of research on the complex new information and communication technologies in the modern economy and law as well as research that explore limits of and opportunities for their usage. The target audience of this book includes undergraduates and postgraduates, university lecturers, experts, and researchers studying various issues concerning the use of new information and communication technologies in modern economies. The book includes research on the following current topics in modern economic science: new challenges and opportunities for establishing information economies under the influence of scientific and technical advances, digital economy as a new vector of development of the modern global economy, economic and legal aspects of using new information and communication technologies in developed and developing countries, priorities of using the new information and communication technologies in modern economies, platforms of communication integration in tourism using new information and communication technologies, and economic and legal managerial aspects and peculiarities of scientific research on the information society.